Understanding the Effect of Structural Diversity in WRKY Transcription Factors on DNA Binding Efficiency through Molecular Dynamics Simulation - Akshay Singh; Ajay Kumar Sharma; Nagendra Kumar Singh; Humira Sonah; Rupesh Deshmukh; Tilak Raj Sharma (Biology, 2019)
A precise understanding of the molecular mechanism involved in stress conditions has great importance for crop improvement. Biomolecules, such as WRKY proteins, which are the largest transcription factor family that is widely distributed in higher plants, plays a significant role in plant defense response against various biotic and abiotic stressors. In the present study, an extensive homology-based three-dimensional model construction and subsequent interaction study of WRKY DNA-binding domain (DBD) in CcWRKY1 (Type I), CcWRKY51 (Type II), and CcWRKY70 (Type III) belonging to pigeonpea, a highly tolerant crop species, was performed. Evaluation of the generated protein models was done to check their reliability and accuracy based on the quantitative and qualitative parameters. The final model was subjected to investigate the comparative binding analysis of different types of WRKY−DBD with DNA-W-box (a cis-acting element) by protein−DNA docking and molecular dynamics (MD) simulation. The DNA binding specificity with WRKY variants was scrutinized through protein−DNA interaction using the HADDOCK server. The stability, as well as conformational changes of protein−DNA complex, was investigated through molecular dynamics (MD) simulations for 100 ns using GROMACS. Additionally, the comparative stability and dynamic behavior of each residue of the WRKY−DBD type were analyzed in terms of root mean square deviation (RMSD), root mean square fluctuation (RMSF)values of the backbone atoms for each frame taking the minimized structure as a reference. The details of DNA binding activity of three different types of WRKY−DBD provided here will be helpful to better understand the regulation of WRKY gene family members in plants.